2018
DOI: 10.1177/0272989x18803109
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Initiating an Insulin Pump in T1D Adults Using Continuous Glucose Monitoring Compared with Multiple Daily Insulin Injections: The DIAMOND Randomized Trial

Abstract: Background: The economic impact of both continuous glucose monitoring (CGM) and insulin pumps (continuous subcutaneous insulin infusion (CSII)) in Type 1 diabetes (T1D) have been evaluated separately. However, the cost-effectiveness of adding CSII to existing CGM users has not yet been assessed. Objective: To evaluate the societal cost-effectiveness of CSII versus continuing multiple daily injections (MDI) in adults with T1D already using CGM. Methods: In the second phase of the DIAMOND trial, 75 adults us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Importantly, our findings demonstrate that the use of rtCGM with MDI can be considered an equivalent but more cost-effective treatment alternative to sensor-augmented insulin pumps for many individuals with T1D. For example, in a recent analysis of the Multiple Daily Injections and Continuous Glucose Monitoring in Diabetes (DIAMOND) trial (8), Skandari and colleagues (27) found that among rtCGM1CSII participants, the total per-person 28-week costs were $8,272 vs. $5,623 among rtCGM1MDI users; the difference was primarily attributed to CSII use. The increasing focus on reducing costs while improving outcomes may impact reimbursement decisions regarding current and future sensor-augmented insulin pump systems.…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, our findings demonstrate that the use of rtCGM with MDI can be considered an equivalent but more cost-effective treatment alternative to sensor-augmented insulin pumps for many individuals with T1D. For example, in a recent analysis of the Multiple Daily Injections and Continuous Glucose Monitoring in Diabetes (DIAMOND) trial (8), Skandari and colleagues (27) found that among rtCGM1CSII participants, the total per-person 28-week costs were $8,272 vs. $5,623 among rtCGM1MDI users; the difference was primarily attributed to CSII use. The increasing focus on reducing costs while improving outcomes may impact reimbursement decisions regarding current and future sensor-augmented insulin pump systems.…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, Wan et al, 19 which was a cost‐effective study of the DIAMOND trial, 15 showed that within‐trial cost‐effectiveness analysis (CEA) when adding CSII to CGM users increased costs with 28‐week costs were $8272 (RT‐CGM+CSII) vs $5623 (RT‐ CGM+MDI), with the difference in costs being attributed to pump use ($2644). In addition, it reduced quality of life, worsened glucose control (higher HbA1c), caused overall clinical harm and increased non‐severe hypoglycaemic events (NSHEs), which was defined as the detection of a glucose value <3.0 mmol/l (<54 mg/dl) for at least 20 consecutive minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CSII systems has resulted in decreased mortality rates and improved quality of life, especially when used in conjunction with rapid-acting insulins. Additionally, users who switch over from multiple daily injections (MDI) to CSII often experience a 20-26% decrease in insulin use [52][53][54]. However, the cost of diabetes care has also risen dramatically within the last few decades, even to the point of posing as an inaccessible barrier to people with diabetes [55,56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%